A reagentless electrochemical immunosensor for sensitive detection of carcinoembryonic antigen based on the interface with redox probe-modified electron transfer wires and effectively immobilized antibody - Zhang, Jing; Yang, Luoxing; Pei, Jie; Tian, Yanzhang; Liu, Jiyang (Frontiers in Chemistry, 2022)
Convenient and sensitive detection of tumor marked in serum samples is of great significance for early diagnosis of cancers. Facile fabrication of label-free electrochemical immunosensor with efficient sensing interface and high sensitivity is highly desirable. Herein, a novel electrochemical label-free immunosensor is demonstrated based on easy fabrication of immunoassay interface with electron transfer wires, confined redox probes and conveniently immobilized antibodies, which can achieve sensitive determination of the tumor marker, carcinoembryonic antigen (CEA). Carboxyl multi-walled carbon nanotubes (MWCNT) are firstly modified with an electrochemical redox probe, methylene blue (MB), which has redox potentials distinguished with those of redox molecules commonly existed in biological samples (e.g. ascorbic acid, uric acid). After the as-prepared MB modified MWCNT (MB-MWCNT) is drop coated on the supporting glassy carbon electrode (GCE), polydopamine (PDA) is in-situ synthesized through simple self-polymerization of dopamine, which act as the biolinker to covalently immobilize the anti-CEA antibody (Ab). The feasibility of the developed immunosensor is validated by electrochemical detection of CEA based on the decrease in the redox signal of MB after specific binding of CEA and immobilized Ab. The fabricated immunosensor can achieve sensitive and label-free detection of CEA ranging from 10 pg/mL to 100 ng/mL with a limit of detection (LOD) of 5.5 pg/mL. Determination of CEA in human serum samples is also realized.